The Recuperation of Enterprises: Defending Workers’ Lifeworld, Creating New Tools of Contention - Itzigsohn, Jose Ezequiel (2016)
Abstract: In the last decade a unique form of struggle developed in Argentina: the appropriationof bankrupt enterprises by their workers. This article combines several sourcesof data to explain the emergence and development of this practice and its effects onArgentine labor politics. We argue that the recuperation of enterprises is the result ofworkers? contingent responses to a deep social crisis, the emergence of organizations thatpromoted this practice, and the presence of a class culture in which wage work is considereda dignifi ed form of work. Furthermore, we argue that the recuperation of enterprisesis now part of the repertoire of contention of Argentine workers.